(untitled) (Global Journal of Human-Social Science, 2017)
Drawing on labour process theory and Bourdieu"s field theory, this study explores the challenges that newspapers face in maintaining their relevance to readers in an age where news has been de-commoditised and made readily available on the web. Empirically the study is based on four case studies of incidents where different newspapers were reported to the Press Ombudsman for inaccurate reporting in recent years. In-depth interviews were conducted with key informants from the selected cases. In addition to that, a key informant from the office of the Press Ombudsman was also interviewed to provide further insight into the effectiveness of the Press Code in regulating accuracy in news reporting as well as the challenges that newspapers are faced with in that regard. It is argued that the digitalisation of media increases the tension between the production of news as a public good vs. its delivery as a commodity that has to ensure profit. Media is an essential pillar of democratic South Africa as it provides news to ensure that citizens are informed about issues that concern them and have the ability to make decisions on matters of concern -i.e. a public good. It is therefore crucial that news be reported in an accurate and professional manner adhering to the standards set by the Press Code. Newspapers are faced with the challenge of ensuring a balance between producing news that is accurate and adheres to the set standards outlined in the Press Code while also ensuring that they remain profitable -i.e. news as a commodity.